MOLECULAR PATHOLOGY OF CEREBROVASCULAR ATHEROSCLEROSIS - Marsetio Donosepoetro (Indonesian Association of Clinical Pathologist and Medical laboratory, 2005)
Cerebrovascular disease are the third most common cause of death in Western countries. The most frequent manifestation of disease is a sudden episode of neurological deficit termed stroke which is the result of cerebral haemorrhage or cerebral infaction in the mayority of cases. Stroke secondary to atherosclerosis is most common in people over 50 years old.The incidence of stroke rises dramatically with ages, with the risk doubling with each decade after 35 years old. About 5 % of people over 65 years old have at least one stroke. Atherosclerosis is condition where fatty acid deposits occur in the inner lining of arteries and the forming of atherosclerotic plaque,a mass consisting of fatty deposit, and blood platelets.The plaque may obstruct or my trigger clot,a trombus,at that location causing cerebral trombosis.It is called ischemmic stroke. The basis of the response to injury hypothesis introduced by Russel Ross is that the earliest cellular events that occur during atherosclerosis is a specialized type of chronic inflammatory response to cell injury. What may begin as a protective inflammatory reponse can become excessive and deleterious to the cell of the artery wall. The adhesion of leucocytes on endothelial cells and their trans –endothelial migration into intima are mediated by adhesion molecules on the endothelial cell membrane that mainly belong to two protein families:the selectin and the addhesion molecules.